= > 2 / 3 = 4 / 6
= > 14 / 5 = 28 / 10
= > 4 / 18 = 2 / 9
= > 12 / 5 = 24 / 10
Ex 27:
a ) 2 / 3 ^ 2 = 4 / 9
2 / 1 : 4 / 9 = 2 / 1 x 9 / 4 = 1 / 1 x 9 / 2 = 9 / 2
11 / 5 : 11 / 10 = 11 / 5 x 10 / 11 = 1 / 1 x 2 / 1 = 2 / 1
9 / 2 + 2 / 1 = 9 / 2 + 4 / 2 = 13 / 2 = 6 , 5
b ) 3 / 1 - 1 / 3 ^2 = 9 / 3 - 1 / 3 = 8 / 3 ^ 2 = 64 / 9
2 / 1 - 1 / 2 ^2 = 4 / 2 - 1 / 2 = 3 / 2 ^2 = 9 / 4
1 1/2 ^2 = 3 / 2 ^ 2 => 9 / 4
64 / 9 + 9 / 4 = 256 / 36 + 81 / 36 = > 337 / 36
337 / 36 - 9 / 4 = 337 / 36 - 81 / 36 = 256 / 36 = 128 / 18 => 64 / 9